Exposure to a 50-Hz magnetic field induced mitochondrial permeability transition through the ROS/GSK-3β signaling pathway. (3rd March 2016) - Feng, Baihuan; Qiu, Liping; Ye, Chunmei; Chen, Liangjing; Fu, Yiti; Sun, Wenjun
Abstract: Purpose To investigate the biological effects of a 50-Hz magnetic field (MF) on mitochondrial permeability. Materials and methods Human amniotic epithelial cells were exposed to MF (50 Hz, 0.4 mT) for different durations. Mitochondrial permeability, mitochondrial membrane potential (ΔΨm), cytochrome c (Cyt-c) release and the related mechanisms were explored. Results Exposure to the MF at 0.4 mT for 60 min transiently induced mitochondrial permeability transition (MPT) and Cyt-c release, although there was no significant effect on mitochondrial membrane potential (ΔΨm). Other than decreasing the total Bcl-2 associated X protein (Bax) level, MF exposure did not significantly affect the levels of Bax and B-cell lymphoma-2 (Bcl-2) in mitochondria. In addition, cells exposed to the MF showed increased intracellular reactive oxidative species (ROS) levels and glycogen synthase kinase-3β (GSK-3β) dephosphorylation at 9 serine residue (Ser 9 ). Moreover, the MF-induced MPT was attenuated by ROS scavenger (N-acetyl-L-cysteine, NAC) or GSK-3β inhibitor, and NAC pretreatment prevented GSK-3β dephosphorylation (Ser 9 ) caused by MF exposure. Conclusion MPT induced by MF exposure was mediated through the ROS/GSK-3β signaling pathway.